The median eye of freshwater mites (Acari: Parasitengonae, Hydrachnidia) and its fate in the stem lineage of the Euhydrachnidia, Witte & Olomski 1991 - Ronald Olomski (Soil Organisms, 2012)
The stem species of freshwater mites (Acari: Hydrachnidia) is generally regarded to be provided with a single median eye which is located below the dorsal cuticle of the prosoma. This character state has been reported from members of the superfamilies Hydrachnoidea, ‘Hydryphantoidea’ and ‘Lebertioidea’. There have been no reports of a median eye from the other five superfamilies until now. In this study, it is shown by histological methods and observations on living specimens: